Working time flexibility in European companies establishment survey on working time 2004-2005 - Chung, Heejung; Kerkhofs, Marcel; Ester, Peter; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2007)
The need for more flexibility is a key element in the current policy debate on the present stance and future of the European economy and labour market. The European Commission believes that Europe has to be less rigid in terms of its institutions, regulations, culture and policies in effectively addressing the fundamental impact of accelerated globalisation processes, increased competition and rapid changes in the demand and supply dynamics (European Employment Taskforce, 2003; European Commission, 2005). In particular, the economic and technological contest with the United States and Asia is a major concern in this context. For Europe to prosper in the 21st century, it needs to become much more flexible in its prime economic, social, cultural and entrepreneurial processes. It thus has to redesign its basic work operations. These new challenges will deeply affect European employer-employee relationships, if only because flexibility directly impacts on existing working time regimes and practices, as well as on the various types of employment contracts. This becomes clear by examining the flexibility arrangements that are currently in place: companies aim to gain a competitive advantage by making production time and opening hours more flexible - for example, by means of non-standard working times, overtime and flexible work contracts - while workers wish to have more flexibility in terms of working time through arrangements such as flexitime, part-time work and various leave schemes. Moreover, workers today are expected to permanently maintain and secure their employability through improving the relevant 'hard' and 'soft' skills, their human capital, thus bringing added value to the organisation. The modern employee, in short, has to become an entrepreneurial employee. Both employers and employees need to take responsibility for their share of flexibility challenges in the workplace. According to the European Employment Taskforce (2003, p. 27): 'Flexibility is not just in the interest of employers. Modern workers also have a need for flexible working arrangements and modern work organisations to help them combine work and care, to make time for education and to respond to their personal preferences and life styles.'
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Flextime -- European Union countries; Business enterprises -- European Union countries; Electronic books